A comprehensive quality improvement model: integrating internal and external information. (3rd April 2022) - Tsai, Ming-Chun; Lin, Shu-Ping; Cheng, Ching-Chan
Abstract : In a highly competitive market, service quality gap, competitor performance and objective assessment of service quality are the key considerations for identifying the critical deficiencies of service quality. This study aims to develop a Competitive Importance-Performance and Gap Analysis (CIPGA) through function conversion, which is based on the relative importance, relative performance and competitive quality gap of each service attribute. The CIPGA model has six strategic patterns, including Competitive advantage, Head-to-Head Competition, Potential Disadvantage, Potential Opportunity, Negative Head-to-Head Competition, and Fatal Crisis. This study takes two major wedding banquet halls in Taiwan as a case study to verify the model. It explores the service quality of the benchmark company compared to the major competitor by setting Wedding Banquet Hall A as the benchmark company and Wedding Banquet Hall B as the major competitor. The results show, for Wedding Banquet Hall A, nine service attributes belong to Potential Opportunity, three service attributes belong to Negative Head-to-Head Competition and three service attributes belong to Fatal Crisis. Their management implications are discussed in detail in the text. This study expects that service quality can be evaluated more specifically and effectively by the CIPGA model, to improve service quality in a highly competitive market.